(untitled) (Harmoni, 2022)
The Indonesian nation has a wealth of traditions that are the cultural treasures of the community. These traditions in the community of their owners turn out to have important meanings that are a source of value for the community in living their lives. The oral tradition in the Brebes community, in the form of the centong war tradition in a series of wedding ceremonies, contains the values of religious moderation. This study aims to reveal the values of religious moderation in the oral tradition in Brebes Regency, especially the tradition of centong war in the wedding procession. This research with a qualitative approach was carried out in Brebes Regency, especially in 3 sub-districts that still carry out the centong war tradition, namely Ketanggungan, Kersana, and Banjarharjo sub-districts. Data was collected by using interview, observation, and documentation methods, especially the recording of the centong war tradition that was uploaded on social media. The results of this study indicate that local traditions contain certain values that can be utilized in the context of contemporary society. The tradition of the centong war as part of the traditional Brebes wedding ceremony procession contains significant values with the current religious problem, namely religious moderation. The tradition of the centong war, which is still preserved by the Brebes people, originates from the traditional Jalawastu tradition in Ciseureuh village, Ketanggungan district, which is located on the slopes of Mount Kumbang. This tradition is inspired by the local story of the conflict between Gandasari and Gandawangi. The values of religious moderation in the centong war tradition include: conflict resolution through a non-violent transformation; social harmony starts from a harmonious family; development of the value of cooperation and generosity; understanding of differences and developing tolerance; and preservation of local culture and wisdom. Although the tradition is called the centong war, this tradition is intended to remind people to avoid conflict and encourage a culture of non-violence. Therefore, the tool used is not a sharp weapon but a rice spoon. This traditional procession can be used to convey messages of strengthening religious moderation and non-violent conflict resolution through the dialogue of the Aki Lengser scene in the centong war tradition.